Changing The World: How Comics and Graphic Novels Can Shift Teaching. Issue 2 (May 2023) - Strong, Myron T.; Cook, Tanya; Belet, Lilika A.; Calarco, Paul
Comic books and graphic novels offer an excellent way to democratize the classroom and improve student learning by giving them the ability to understand social issues and social institutions in a relatable way. This article is a conversation exploring the validity of comics as tools to teach sociology. Specifically, the article does this through examining the effectiveness of comics as a way to analyze gender, the looking glass self, and the sociological imagination and exploring the use of graphic novels to replace traditional texts in the introductory sociology classroom. If one of our disciplinary goals is to change society for the better by boosting the development of sociological imaginations, looking at comics may give us the best format to do so.